DRIVING FACTORS OF WOMEN BUSINESS PERFORMANCE IN CREATIVE ECONOMIC INDUSTRY - Lina Salim; Ari Setiyaningrum (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2022)
This study aims to examine the driving factors of business performance managed by women entrepreneurs in the creative economy industry. The study was conducted by collecting primary data through the distribution of questionnaires to 185 women entrepreneurs in the DKI Jakarta area. Sampling method using non-probability sampling with purposive sampling technique. The research data were analyzed using descriptive statistical analysis and multiple linear regression analysis. The results of the study indicated that the strongest driving factor of business performance managed by women entrepreneurs is the business environment followed by socio-cultural, training and development, motivation, and networking. The financial factor is the only factor that does not drive the business performance of women entrepreneur.